(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Anti-Müllerian hormone (AMH) has emerged as one of the most reliable biomarkers of ovarian reserve and reproductive potential, particularly in women undergoing assisted reproductive technologies (ART) such as in vitro fertilization (IVF). Unlike traditional markers such as follicle-stimulating hormone (FSH) or estradiol, AMH demonstrates minimal intra-cycle variation and provides a more consistent reflection of the pool of antral and pre-antral follicles. This study explores the relationship between serum AMH levels and IVF success, focusing on ovarian response, oocyte yield, embryo quality, and clinical pregnancy outcomes. Women undergoing IVF were stratified into three categories based on AMH concentration: low (<1 ng/mL), normal (1–3.5 ng/mL), and high (>3.5 ng/mL). Results indicate that AMH strongly correlates with ovarian response; women with higher AMH levels produced a greater number of mature oocytes, resulting in more embryos available for transfer. However, the predictive value of AMH for clinical pregnancy and live birth was moderate, suggesting that while AMH is a robust marker of quantity, it may not fully reflect oocyte or embryo competence. Interestingly, extremely high AMH levels were associated with increased ovarian hyperstimulation risk, underscoring the importance of individualized stimulation protocols. Findings align with recent literature between 2016 and 2022, which consistently highlights AMH as a key determinant in guiding ovarian stimulation strategies, counseling couples about IVF prognosis, and reducing treatment dropouts. For instance, studies by Tal et al. (2021) and Iliodromiti et al. (2017) reported that AMH is an excellent predictor of ovarian response but only a fair predictor of live birth, emphasizing the multifactorial nature of fertility outcomes. Integrating AMH measurement with antral follicle count (AFC) and other clinical parameters provides a more holistic approach to predicting IVF success. AMH remains an invaluable biomarker in reproductive endocrinology. It provides clinicians with critical insights into ovarian reserve, supports individualized IVF treatment, and helps manage patient expectations. Nevertheless, AMH alone should not be considered a definitive predictor of pregnancy or live birth, as factors such as age, body mass index, lifestyle, and endometrial receptivity also play significant roles. Future research should focus on combining AMH with genomic and metabolic markers to develop more precise predictive models for IVF success.